Current attitude to deferral of cellular therapy or nontransplant chemotherapy due to SARS‐CoV‐2 asymptomatic infection: Survey of Infectious Diseases Working Party EBMT. Issue 2 (31st January 2022) - Styczynski, Jan; Cesaro, Simone; von Lilienfeld‐Toal, Marie; Marchesi, Francesco; Gil, Lidia; Mikulska, Malgorzata; Knelange, Nina; Wendel, Lotus; Averbuch, Diana; de la Camara, Rafael
Abstract: The objective of the study was to assess the current clinical practice and the attitude toward deferral of HCT/chemotherapy in patients with hematological diseases in cases of asymptomatic patients with a positive assay for SARS‐CoV‐2. In August 2021, we performed a survey among EBMT centers regarding their attitude toward deferral of HCT/chemotherapy in patients with a positive PCR result. Centers were willing to defer the planned cellular therapy for patients with asymptomatic SARS‐CoV‐2 infection without previous COVID‐19 disease, and patients who became asymptomatic after a previous COVID19 disease but persistently shed the virus, respectively, in case of high‐risk allo‐HCT (90.2%/76.9%), low‐risk allo‐HCT for malignant diseases (88.2%/83.7%), allo‐HCT for nonmalignant diseases (91.0%/91.0%), auto‐HCT (88.0%/79.8%), and CAR‐T therapy (83.1%/81.4%). The respective rates toward deferral of noncellular therapy patients was lower for both groups of patients, and varied with the primary diagnosis and anti‐malignant treatment. There is a relatively high rate of willingness to defer treatment in asymptomatic patients being positive for SARS‐CoV‐2, planned for cellular therapy, regardless of previous history of vaccination or COVID‐19. The same approach is presented for most of patients before noncellular therapy. Nevertheless, each patient should be considered individually weighting risks and benefits.